Making sense of energy management practice: reflections on providing low carbon support to three SMEs in the UK - Hampton, S (Springer Netherlands, 2018)
Energy consumption by small and medium-sized enterprises (SMEs) is collectively significant, and whilst opportunities for substantial, cost-effective efficiency savings exist, take up is low. Whereas research tackling this challenge typically focuses on barriers and drivers to action, this paper offers an alternative perspective, investigating energy management as a practice. Drawing on practice theory and the concept of organisational sensemaking, narrative accounts provide in-depth insights into energy management practice within three SMEs. Auto-ethnographic reflections from 5 years of providing energy and environmental advice are supplemented by findings from carbon footprint assessments and interviews. Findings show that despite energy management being perceived as a peripheral business activity, it is intertwined with organisational identity and knowledge production in each of the three SMEs. Business advisors are instrumental in steering SME energy management practices and have a responsibility to reflect on how they influence processes of knowledge production and meaning-making in organisations. Implications for policy-makers, advisors and the research community are discussed.